2001
DOI: 10.1074/jbc.m011303200
|View full text |Cite
|
Sign up to set email alerts
|

The Ataxia telangiectasia Gene Product Is Required for Oxidative Stress-induced G1 and G2Checkpoint Function in Human Fibroblasts

Abstract: Ataxia telangiectasia (AT) is an autosomal recessive disorder characterized by neuronal degeneration accompanied by ataxia, telangiectasias, acute cancer predisposition, and sensitivity to ionizing radiation (IR). Cells from individuals with AT show unusual sensitivity to IR, severely attenuated cell cycle checkpoint functions, and poor p53 induction in response to IR compared with normal human fibroblasts (NHFs). The gene mutated in AT (ATM) has been cloned, and its product, pATM, has IR-inducible kinase acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
80
0
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(87 citation statements)
references
References 38 publications
5
80
0
2
Order By: Relevance
“…This, however, is not the case, as patients with AT exhibit hypersensitivity to IR and a reduced ability to respond appropriately to oxidative challenge (Lavin and Shiloh, 1997;Gatei et al, 2001). In response to oxidative challenges or DNA damage, AT cells show reduced induction of p53 protein and p53 phosphorylation, and they fail to show G1/S and G2/M cell cycle checkpoints as compared to cells with wild type ATM (Shackelford et al, 2001). It is the loss of these critical p53-dependent checkpoint functions that is believed to render AT cells hypersensitive to IR.…”
Section: Ataxia-telangiectasia Mutated (Atm) Kinasementioning
confidence: 99%
“…This, however, is not the case, as patients with AT exhibit hypersensitivity to IR and a reduced ability to respond appropriately to oxidative challenge (Lavin and Shiloh, 1997;Gatei et al, 2001). In response to oxidative challenges or DNA damage, AT cells show reduced induction of p53 protein and p53 phosphorylation, and they fail to show G1/S and G2/M cell cycle checkpoints as compared to cells with wild type ATM (Shackelford et al, 2001). It is the loss of these critical p53-dependent checkpoint functions that is believed to render AT cells hypersensitive to IR.…”
Section: Ataxia-telangiectasia Mutated (Atm) Kinasementioning
confidence: 99%
“…The antibody to phospho-ATM (Ser 1981 ) was from Rockland Immunochemicals. The antiserum to total ATM was generated in our laboratory (21); alternatively, we also used anti-ATM purchased from Bethyl. The antibody to phospho-DNA-PKcs (Thr 2609 ) was from Abcam.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown by numerous investigators that ATM-deficient cells are hypersensitive to IR-induced clonogenic lethality. Shackelford et al (15) showed that GM03395 ATMϪ/Ϫ and GM02052 ATM mutant cells exhibit increased sensitivity to IR-induced clonogenic lethality compared with normal human fibroblasts. Furthermore, using neocarzinostatin (generous gift of Dr. Irving Goldberg, Harvard Medical School), a radiomimetic agent, we found that 10 and 25 ng/ml neocarzinostatin caused 82 and 35% clonogenic survival in GM03440 ATMϩ/ϩ cells, but only 40 and 7% in GM03395 ATMϪ/Ϫ cells (data not shown).…”
Section: Atm-deficient Cells Fail To Exhibit Checkpoint Arrest In Earmentioning
confidence: 99%